2020
DOI: 10.1186/s13046-020-01664-1
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA ZFPM2-AS1 acts as a miRNA sponge and promotes cell invasion through regulation of miR-139/GDF10 in hepatocellular carcinoma

Abstract: Background Emerging evidence has shown that dysregulated expression of long noncoding RNAs (lncRNAs) is implicated in liver hepatocellular carcinoma (HCC). However, the role and molecular mechanism of differentially expressed lncRNAs in HCC has not been fully explained. Methods The expression profiles of lncRNAs in HCC samples were derived from microarrays analysis or downloaded from The Cancer Genome Atlas (TCGA), and their correlation with prognosis and clinical chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 33 publications
(39 reference statements)
3
57
0
Order By: Relevance
“…For example, Zhe Li et al reported that LINC00624 enhances liver cancer progression by disrupting the histone deacetylase 6 (HDAC6)- tripartite motif containing 28 (TRIM28) - zinc finger potein 354C (ZNF354C) corepressor complex [ 6 ]. Hui He et al confirmed that lncRNA ZFPM2-AS1 acts as a miRNA sponge and promotes cell invasion through regulation of miR-139/growth differentiation factor 10 (GDF10) in HCC [ 7 ]. Our research team also discovered and studied the role of several lncRNAs in the progression of HCC in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhe Li et al reported that LINC00624 enhances liver cancer progression by disrupting the histone deacetylase 6 (HDAC6)- tripartite motif containing 28 (TRIM28) - zinc finger potein 354C (ZNF354C) corepressor complex [ 6 ]. Hui He et al confirmed that lncRNA ZFPM2-AS1 acts as a miRNA sponge and promotes cell invasion through regulation of miR-139/growth differentiation factor 10 (GDF10) in HCC [ 7 ]. Our research team also discovered and studied the role of several lncRNAs in the progression of HCC in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have indicated that lncRNAs are aberrantly expressed and serve as diagnostic and prognostic biomarkers in HCC (40)(41)(42). LncRNA DUXAP8, as an oncogene, is dysregulated in multiple tumors, such as bladder cancer ( 13), non-small-cell lung cancer (43) and ovarian cancer (44).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, additional studies showed the existence of a large number of stable miRNAs in human serum/plasma, which laid the foundation for studying the role of serum/plasma microRNAs in the diagnosis and prognosis of HCC [80][81][82][83]. Differential expression of several serum microRNAs, including miR-16, miR122, miR-21, miR-223, miR-25, miR-375, and let-7f, in patients with HCC, patients with hepatitis B, and healthy individuals was reported recently [84][85][86][87].…”
Section: Discussionmentioning
confidence: 99%